Analysis of Linguistic Errors in Students' Speaking Skill at Al-Qodiri Junior Secondary School 1 Jember - Jannah, Siti Alfiatul; Bin Madi, Faisol Nasar; Rosyid, Abdur (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
Language skills will be more optimal if supported by a supportive language environment and habituation. However, the high intensity of language use will be prone to causing language errors, which needs to be identified and a solution found so that it does not happen again. This research aims to determine and analyze the forms of students' language errors at MTs Unggulan Al-Qodiri 1 Jember and the factors behind them. The approach used is a qualitative method with a field study type. The data collection method uses observation, interviews and documentation, as well as the data analysis method using the Miles and Huberman model which consists of data reduction, data display and conclusions. The research results show that students' language errors in maharah kalam often occur in the pronounciation of fiil madli, mudhori’ dan amrand the pronunciation of muannats and mudzakkar sentences. Meanwhile, the factors that cause language errors are mother tongue, environment, interlingual interference and intralingual interference. Abstrak Kemampuan berbahasa akan lebih optimal bila didukung adanya lingkungan berbahasa dan pembiasaan yang mendukung. Namun, tingginya intensitas penggunaan bahasa akan rentan menimbulkan kesalahan berbahasa, sesuatu yang perlu diidentifikasi dan dicarikan solusi agar tidak terjadi lagi ke depannya. Penelitian ini bertujuan untuk mengetahui dan menganalisis bentuk kesalahan berbahasa siswa di MTs Unggulan Al-Qodiri 1 Jember serta faktor-faktor yang melatar belakanginya. Pendekatan yang digunakan adalah metode kualitatif dengan jenis studi lapangan. Metode pengumpulan data menggunakan observasi, wawancara dan dokumentasi, serta metode analisis data menggunakan model Miles and Huberman yang terdiri dari reduksi data, display data dan kesimpulan. Hasil penelitian menunjukkan bentuk kesalahan berbahasa siswa dalam maharah kalam banyak terjadi dalam pengucapan fiil madli, mudhori’ dan amr dan pengucapan kalimat muannats dan mudzakkar. Sedangkan faktor penyebab kesalahan berbahasa yaitu bahasa ibu, lingkungan, interferensi interlingual dan interferensi intralingual.